Rotating Radio Transients: new discoveries, timing solutions and musings - Keane, E. F.; Kramer, M.; Lyne, A. G.; Stappers, B. W.; McLaughlin, M. A. (Monthly notices of the Royal Astronomical Society, 2011)
We describe observations of Rotating Radio Transients (RRATs) that were discovered in a re-analysis of the Parkes Multibeam Pulsar Survey (PMPS). The sources have now been monitored for sufficiently long to obtain seven new coherent timing solutions to make a total of 14 now known. Furthermore, we announce the discovery of seven new transient sources, one of which may be extragalactic in origin (with z∼ 0.1) and would then be a second example of the so-called 'Lorimer burst'. The timing solutions allow us to infer neutron star characteristics such as energy-loss rate, magnetic field strength and evolutionary time-scales, as well as facilitating multiwavelength followup by providing accurate astrometry. All of this enables us to consider the question of whether or not RRATs are in any way special, i.e. a distinct and separate population of neutron stars, as has been previously suggested. We see no reason to consider 'RRAT' as anything other than a detection label, the subject of a selection effect in the parameter space searched. However, single-pulse searches can be utilized to great effect to identify pulsars difficult, or impossible, to find by other means, in particular those with long periods (half of the PMPS RRATs have periods greater than 4 s), high magnetic field strengths (B≳ 1013 G) and pulsars approaching the 'death valley'. The detailed nulling properties of such pulsars are unknown but the mounting evidence suggests a broad range of behaviour in the pulsar population. The group of RRATs fits in to the picture where pulsar magnetospheres switch between stable configurations.